hasil penelitian PENGUATAN PENDIDIKAN KARAKTER MELALUI PROGRAM “GELISIK” BERBASIS LITERASI INTERAKTIF DAN REFLEKTIF DI SEKOLAH DASAR - Angres Sugiarti; Wildan Nurul Fajar; Hotlan Richardo Purba (STKIP Subang, 2026)
This study explores the implementation of the GELISIK Program (Gerakan Literasi Asyik) in strengthening character education among fifth-grade students at SD Negeri Tayem 02 Karangpucung, Cilacap. The program was developed to transform the fifteen-minute reading habit before learning into interactive and reflective literacy activities through paired reading, digital storytelling, story mapping, read aloud, role play, and literacy journals. This study employed a qualitative approach with a case study design involving 17 fifth-grade students, a classroom teacher, a principal, and supporting teachers. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of data reduction, data display, conclusion drawing, and verification. The findings showed that GELISIK improved students’ participation in literacy activities and strengthened curiosity, responsibility, confidence in expressing opinions, collaboration, and reading interest. Supporting factors included teachers’ roles, students’ enthusiasm, varied reading materials, digital facilities, and school support. Challenges included differences in reading ability, students’ shyness, limited implementation time, and shared use of digital facilities. These challenges were addressed through heterogeneous grouping, peer assistance, gradual performance opportunities, flexible scheduling, and printed reading materials as alternatives. The GELISIK Program demonstrates that interactive and reflective literacy habituation can serve as an effective strategy for strengthening character education in elementary schools.